Bottom Current Modification of Turbidite Lobe Complexes - Fuhrmann, A.; Kane, I. A.; Schomacker, E.; Clare, M. A.; Pontén, Anna (Frontiers in Earth Science, 2022)
Submarine lobes form at the distal end of sediment gravity flow systems and are globally important sinks for sediment, anthropogenic pollutants and organic carbon, as well as forming hydrocarbon and CO2 reservoirs. Contour currents can modify gravity flow pathways and sediment distribution by directly interacting with the flow or by modifying seafloor morphology. Deciphering the nature of gravity- and contour-current interaction, particularly in ancient systems, remains a challenge due to the lack of integrated datasets and the necessary oceanographic framework. Here we analyse high-resolution 3D seismic reflection and core data from the Upper Cretaceous interval offshore Tanzania to reveal the interaction of turbidite lobes with fine-grained sediment waves and contourite drift deposits. Contourite drift morphology governs the large-scale confinement style and shape of lobes that range from frontally confined and crescent shaped, to laterally confined and elongated, to semi-confined lobes. Core data reveals massive to cross-laminated high density turbidites in the lobe axis position that show no direct interaction between gravity flows and contour currents. Lobe off-axis and fringe deposits consist of parallel- and ripple-laminated, low density turbidites, which are inter-bedded with bioturbated, muddy siltstones that represent contourite drifts. Starved ripples, and streaks of up to fine-grained sandstone above individual turbidite beds indicate reworking by contour currents. This facies distribution reflects the temporal interaction of quasi-steady bottom currents and turbidity currents that interact with the topography and build lobes over short periods of time. Frontally confined turbidity currents form lobes in a fill-and-spill fashion, in which the confinement of turbidity currents causes rapid deposition and obscures any bottom current signal. Lateral confinement causes increased turbidity current runout length, and promotes the development of lobe fringes with a high proportion of bottom current reworked sands. During times when sediment gravity flows are subordinate, contourite deposits deposit on top of the lobe, confining the next flow and thus modify the overall stacking pattern of the lobe complex. Although sediment volumes of lobe complexes are comparable to other deep-marine systems, bottom currents considerably influence facies distribution and deposit architecture.